Pemodelan dan Evaluasi Jaringan Distribusi Air Bersih Menggunakan EPANET 2.2 pada PDAM Tirta Ayumi Kota Padangsidimpuan - Muhammad Parholongan Harahap; Mhd. Rahman Rambe; Rizky Febriani Pohan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
This research was conducted on the clean water distribution network of PDAM Tirta Ayumi in Padangsidimpuan City. PDAM Tirta Ayumi serves two districts, namely Padangsidimpuan Batunadua District and Padangsidimpuan Tenggara District. The purpose of this study is to simulate and analyze the clean water distribution network of PDAM Tirta Ayumi Padangsidimpuan City using the Epanet 2.2 software. The data collection technique applied in this research was the literature study method. The results of the simulation analysis of the clean water distribution network in the service area of PDAM Tirta Ayumi Padangsidimpuan City, particularly in Padangsidimpuan Batunadua District and Padangsidimpuan Tenggara District, using the Epanet 2.2 software indicate that several parameters at the link and node in each management area have not met the required values based on the referenced standards. Therefore, updates or adjustments to the link and node in each management area are necessary to ensure that the parameters meet the required standards, thereby optimizing the simulation design of the PDAM Tirta Ayumi clean water distribution network.